Land reclamation - from conventional vertical drain methods to a combined vacuum preloading and electro-osmosis with horizontal drainage enhanced geotextile sheets - Wong, Lung Anthony (Nanyang Technological University, 2023)
Sandy soil is an ideal backfill material for land reclamation. However, sandy soil in particular hydraulically dredged sand is depleting. Slurry of soft marine deposits dredged from the seabed has increasingly been used in various land reclamation projects in recent years. However, the geotechnical properties of clay slurry are poor and soil improvement is required during land reclamation. The major challenges include the extra time required for consolidating the clay slurry and the formation of a working platform for construction, which are not necessary if sandy fill material is adopted. Consolidation analysis of drained reclamation work is a key aspect in assessing the performance of the ground improvement work conducted. Field data from a recent land reclamation project, namely Tung Chung New Town Extension, in Hong Kong have been comprehensively reviewed, which covers the assessment of the consolidation behavior of soft marine clay with prefabricated vertical drains. This analysis provides data on the performance of conventional ground improvement method using PVDs, which sets the scene for a comparison of the efficiency of the traditional method and the proposed novel method of vacuum preloading. In order to reduce the time to consolidate the clay slurry, vacuum preloading with horizontal drainage enhanced geotextile (HDeG) sheets is proposed. In contrast with the previous studies reported in the literature, the test plan proposed in this study allows a systematic investigation on the effect of the configuration of HDeG in accelerating the consolidation of clay slurry. Four model tests have been conducted which have showed that the performance of HDeG is effective. Furthermore, an analytical solution for the consolidation analysis of vacuum preloading using HDeG has also been validated using the model test results. A technical feasibility study on the potential use of vacuum preloading of clay slurry with HDeG in a real-scale land reclamation project has been conducted. Instead of using fictitious geological conditions and soil properties, the geological setting of an actual project, i.e., Tung Chung Project, has been adopted. The boundary conditions of this case study are the same as the Tung Chung New Town Extension Project, except that vacuum preloading of multi-layers of clay slurry instead of mechanical compaction of rockfill has been used. Two design schemes of land reclamation involving the use of 12 m thick clay slurry for the full depth (i.e. Scheme S1) and 4 m thick clay slurry above the sea level (i.e. Scheme S2) have been analysed. Based on the validated design methods, all clay slurry can be consolidated to a water content that is lower than the liquid limit in both schemes. As a result, there is a significant reduction in the consumption of rockfill in the trial embankment, as compared with the traditional method adopted in the field. The reuse of clay slurry in land reclamation alongside vacuum preloading with HDeG is thus technically feasible. To further enhance the performance of HDeG, a two-phased experimental investigation of the effectiveness of the combined vacuum preloading and electro-osmosis with e-HDeG has been carried out. Carbon felt electrodes have been adopted and a current of 2.0 A has been used. Based on the results of the miniature tests conducted, a late activation of electro-osmosis results in a better consolidation performance when it is coupled with vacuum preloading. The performance of this combined method has been further tested in a more realistic scale, in which electro-osmosis was activated, while vacuum pressure was maintained, when the average degree of consolidation of the clay slurry reached 70%. In summary, the electro-osmosis serves as a booster to the vacuum preloading using HDeG as it accelerates the consolidation and further improves the properties of clay slurry. The effect of electro-osmosis is estimated to be equivalent to a 47 kPa additional surcharge which further speeds up the consolidation process.